Calcium pyrophosphate dihydrate deposition disease in the temporomandibular joint: diagnosis and treatment - Kwang-Jun Kwon; Hyun Seok; Jang-Ha Lee; Min-Keun Kim; Seong-Gon Kim; Hyung-Ki Park; Hang-Moon Choi (SpringerOpen, 2018)
Abstract Background Calcium pyrophosphate dihydrate deposition disease (CPDD) is a rare disease in the temporomandibular joint (TMJ) space. It forms a calcified crystal mass and induces a limitation of joint movement. Case presentation The calcified mass in our case was occupied in the left TMJ area and extended to the infratemporal and middle cranial fossa. For a complete excision of this mass, we performed a vertical ramus osteotomy and resected the mass around the mandibular condyle. The calcified mass in the infratemporal fossa was carefully excised, and the segmented mandible was anatomically repositioned. Scanning electronic microscopy (SEM)/energy-dispersive X-ray spectroscopy (EDS) microanalysis was performed to evaluate the calcified mass. The result of SEM/EDS showed that the crystal mass was completely composed of calcium pyrophosphate dihydrate. This result strongly suggested that the calcified mass was CPDD in the TMJ area. Conclusions CPDD in the TMJ is a rare disease and is difficult to differentially diagnose from other neoplasms. A histological examination and quantitative microanalysis are required to confirm the diagnosis. In our patient, CPDD in the TMJ was successfully removed via the extracorporeal approach. SEM/EDS microanalysis was used for the differential diagnosis.